Effectiveness of Evidence-Based Learning Strategy for Enhancing Cyber Security Awareness of Higher Secondary Students - Bindu D.; Kumari Sandra C. S. (Integrated Journal for Research in Arts and Humanities, 2023)
Learning based on evidence and empirical data always make students more involved in the content area and help to conceptualise how to take decisions, based on tangible evidence offered by both scientific literature and experiments, or by data and information obtained through various procedures. This is the era where digital natives inhabit and immerse in Google world for every single need and deed which may results in intentional or unintentional engagements in several social media platforms that may lead to serious cyber threats and issues, even crimes. The present experimental study analysed the effectiveness of Evidence based learning strategy for enhancing cyber security awareness among higher secondary students. From a total sample of 100 higher secondary students, 50 each were randomly selected as control and experimental groups and are given learning experience through ongoing activity-based method and Evidence based learning strategy respectively. Pre-test and post-test on cyber security awareness were conducted and results obtained were statistically analysed through mean, standard deviation, and t-test. Result of the study revealed that the group instructed through evidence-based learning strategy showed significantly higher level of awareness than the group instructed through ongoing method.